Gendered decision-making and the drivers of seed choice in Andhra Pradesh and Telangana - Goundla, Mamatha; Rajshekar, G.; Ramanjaneyulu, G.V.; Veluguri, Divya (Center for Sustainable Agriculture, India, 2023)
Seeds play a critical role in agriculture, affecting biodiversity and food security. This study focuses on understanding the factors influencing seed source and varietal choices, with an emphasis on the gendered nature of decision-making, as part of a larger project aiming to establish gender-responsive, decentralized, open-source seed systems in Andhra Pradesh and Telangana. Data collection is ongoing, and nine focus group discussions (120 men, 82 women) have been conducted thus far. The findings suggest that women’s role in seed selection varies across regions and crops. In tribal communities, women are custodians of seeds and reported significant influence over seed varietal choices and replacement, preferring to store seeds, whenever possible. In central Telangana, where farmers cultivate market-focused crops, women rarely participate in seed selection activities, despite being integral to agricultural operations. In regions growing high-input, market-focused crops, where women report contributing to discussions on seed-related choices, the final decision often rests with the family head. Women respondents often reported that male decision-makers preferred sourcing seed from input shops. Farmers primarily rely on input shops and nurseries for sourcing seeds or saplings, but they acquired seeds from staterun universities, farmer producer organizations and fellow farmers. Few farmers reported storing seeds, with storage primarily limited to self-pollinated crops that are easy to store and less susceptible to pests. This study illuminates the multifaceted dynamics of seed systems in Andhra Pradesh and Telangana, and highlights the disparity in women’s involvement in seed selection across regions.